Efektivitas Metode Problem Based Learning Terhadap Kemampuan Berpikir Kritis : Studi Literatur - Maharani, Septia (Papanda Journal of Mathematics and Science Research, 2024)
Education can be said to be the main goal that must be owned by humans, and self-potential can be developed through education and humans are able to become the next successor. Improving the quality of education can be done by using appropriate learning methods so as to improve students' abilities, one of which is the ability to think critically. This study aims to determine the effectiveness of the Problem Based Learning learning method on critical thinking skills. The method used in this study is a literature study by collecting some relevant data for the last 4 years with the population, namely elementary school students. Data collection was used in this study through Google, Google Shoolar, ScienceDirect and Springer. Based on the data that has been reduced and described, it can be concluded that the Problem Based Learning method has proven effective in improving the critical thinking skills of elementary school students.